The Overview of Student Knowledge about The Importance of Inverted Pyramid Antenatal Care at Faculty of Medicine, Universitas Sumatera Utara: Gambaran Pengetahuan Mahasiswa tentang Pentingnya Antenatal Care Piramida Terbalik di Fakultas Kedokteran, Universitas Sumatera Utara - Billy Putra Teruna; Dudy Aldiansyah; Hilma Putri Lubis; Rozaimah Zain-Hamid (Sumatera Medical Journal, 2022)
Introduction. The old model antenatal care/simple pyramid in 1929 based on the third trimester, contributed substantially to the reduction of maternal and newborn mortality. Along with the development of science and technology, many complications of pregnancy including fetal abnormalities, miscarriage, stillbirth, preeclampsia, premature delivery, gestational diabetes, fetal growth disorders, and macrosomia can be detected in the first trimester. Therefore, the inverted pyramid antenatal care was developed with early detection of risk factors and complications at 11-13 weeks of gestation. However, the application of the inverted pyramid antenatal care in Indonesia has not been implemented and there is a lack of socialization about the importance of the inverted pyramid antenatal care. Objectives. The purpose of this research was to describe knowledge about importance of inverted pyramid antenatal care in student generation 2018-2020 of Faculty of Medicine Universitas Sumatera Utara. Methods. This research used a descriptive analytic study with cross sectional approach and primary data was collected using online questionnaire. Results. There is no significant difference about descriptions of knowledge between student of 3rd semester, 5th semester. and 7th semester. From 126 subjects, 77 subjects (61,1%) use more than one source of information. Conclusion. Student of generation 2018-2020 of Faculty Medicine Universitas Sumatera Utara have a good knowledge about the importance of inverted pyramid antenatal care by involving more than one source of information